Peripartum Abdominal Compartment Syndrome Following Extracorporeal Hemodynamic Support - Lozovyy, Violetta; Saoud, Fawzi; Pacheco, Luis D. (American Journal of Perinatology Reports, 2024)
In massive pulmonary embolism (PE), anticoagulation and thrombolytics may increase the risk of retroperitoneal bleeding following vascular cannulation for extracorporeal hemodynamic support resulting in abdominal compartment syndrome (ACS). A 27-year-old women at 33 weeks of gestation presented with acute chest pain and shortness of breath. Massive PE was diagnosed. Intravenous unfractionated heparin was started together with catheter-directed tissue plasminogen activator (tPA) infusion and mechanical thrombectomy. During the procedure, cardiac arrest developed. Cardiopulmonary resuscitation, intravenous tPA, and urgent perimortem cesarean delivery were performed. After return of spontaneous circulation, profound right ventricular failure required venoarterial membrane oxygenation. Six hours afterward, ACS secondary to retroperitoneal bleeding developed, requiring surgical intervention. ACS may result from retroperitoneal bleeding following cannulation for extracorporeal hemodynamic support.
Keywords: C-section; complications; pulmonary embolism; ECMO